Facile synthesis of mechanically flexible and super-hydrophobic silicone aerogels with tunable pore structure for efficient oil-water separation. (December 2022) - Qu, Yong-Xiang; Guo, Kun-Yu; Pan, Hong-Tao; Wu, Zhi-Hao; Guo, Bi-Fan; Feng, Xiao-Lan; Kong, Ting-Ting; Zhang, Chao; Zhang, Guo-Dong; Zhao, Li; Gong, Li-Xiu; Gao, Jie-Feng; et al.
Abstract: Silicone aerogels are promising in efficient thermal insulating and oil absorbent materials due to the low density, low thermal conductivity, and unique micro-/nano- porous structure. However, poor mechanical reliability and water repellency along with the complicated processing greatly hinder their potential applications in emerging fields. Herein, we report a lightweight, wide-temperature mechanically flexible and surface super-hydrophobic silicone aerogels with tuned cross-linked network via a facile ambient drying process. Poly (methylhydridosiloxane) (PMHS) with different hydrogen contents was utilized to react with vinylmethyldimethoxysilane under Pt catalyst via hydrosilylation reaction and thus tune the cross-linking network in silicone aerogel effectively. The optimized PMHS-based silicone aerogels as-prepared exhibit a low density of 70–150 mg cm −3, good mechanical reliability in both liquid nitrogen and high-temperature condition of 200 °C, excellent compressive resilience after 100 cyclic compressions, and outstanding surface water repellency with water contact angle of ∼165° and water sliding angle of <3°. As expected, such multi-functional PMHS aerogels show a better thermal insulating performance than the commercial polymer foam materials. Furthermore, the as-prepared silicone aerogels not only display outstanding absorption capacity for both floating and sunken oil/solvent but also demonstrate excellent continuous oil/water separation efficiency. Clearly, the versatile PMHS-based aerogel prepared in this work may provide a new route for the design and development of high-performance silicone aerogel materials. Graphical abstract: Image 1 Highlights: Tunable poly(methylhydridosiloxane)-based silicone aerogels are prepared via a facile ambient drying process. The poly(methylhydridosiloxane)-based aerogels show wide-temperature mechanical flexibility and reliability. The optimized aerogel exhibits excellent super-hydrophobicity with water contact angle of >160°. Efficient oil/solvent absorption and continuous oil-water separation were obtained.